Utilization of Maternity Waiting Homes in the Islands: A Study Literature: Pemanfaatan Rumah Tunggu Bersalin di Kepulauan: Studi Literatur - harianja, ristinarosauli; Mardiah; Batubara, Kartika Sri Dewi (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2022)
The maternal mortality rate is still high in Indonesia, especially in the archipelago, and shows a low level of health. A Maternity Waiting Home (MWH) is a place or room near a health facility (hospital, health center, poskesdes) that can be used as a temporary residence for pregnant women and their companions (husband/cadre/shaman/family) for several days while waiting for delivery and a few days after giving birth. A literature review using the narrative literature review method was carried out by synthesizing and analyzing 3 scientific article search engines. Searching for manuscripts on the three search engines found 6 manuscripts that match the specified topic, namely the use of birth waiting homes for mothers in the islands. The results of the literature review showed that several factors influence the use of MWH, including distance to health facilities, travel time, socio-economic conditions of the community, completeness of MWH  facilities, and community participation. Efforts to utilize this MWH are expected to increase access to health services, and the number of deliveries to incompetent health care facilities and can reduce cases of complications for pregnant women, maternity mothers, postpartum mothers, and newborns.